Mutations and polymorphisms in N-acetylgalactosamine-6-sulfate sulfatase gene in Turkish Morquio A patients - ELÇİOĞLU, HURİYE NURSEL (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2014)
Mucopolysaccharidosis type IVA (MPS IVA) is an autosomal recessive inherited metabolic disease resulting from deficiency of N-acetylgalactosamine-6-sulfatase (GALNS). This lysosomal storage disorder leads to a wide range of clinical variability ranging from severe, through intermediate to mild forms. The classical phenotype of Morquio A disease is characterized by severe bone dysplasia without intellectual impairment. Two severe MPS IVA patients from two unrelated Turkish families have been investigated. The 14 exons and intron-exon junctions of the GALNS gene were sequenced after amplification from genomic DNA. Direct sequencing revealed two homozygous mutations previously described: p.L390X in exon 11 and p.W141R in exon 4. The p L390X mutation was associated with four novel polymorphisms in intron 2, intron 5 and intron 6 and one polymorphism previously described in exon 7. We have analysed the haplotypes associated with the two identified mutations. These molecular findings will permit accurate carrier detection, prenatal diagnosis and counseling for Morquio A syndrome in Turkey. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Mucopolysaccharidosis type IVA; GALNS; Mutations; Polymorphisms; Consanguinity; MUCOPOLYSACCHARIDOSIS IVA; MISSENSE MUTATIONS; GALNS GENE; SPECTRUM; DISEASE